Evaluation of arterial stiffness in patients with schizophrenia - Baykara, Sema; Bozdag, Pinar Gundogan; Baykara, Murat; Namli, Mustafa Nuray (Elsevier Sci Ltd, 2020)
The aim of this study was to evaluate arterial stiffness in schizophrenia patients. 28 male patients were included. The intima-media thickness (IMT) of the vessels were taken using high-resolution ultrasonography system. The mean carotid IMT and the mean femoral IMT values of the study group were found to be statistically significantly higher than the values of the control group. As the duration of the disease increased, there was an increase in the carotid IMT, carotid elastic modulus and femoral IMT, whereas there was a decrease in carotid and femoral diastolic wall stress in patients. No statistically significant differences were observed between the groups' carotid and femoral compliance, distensibility and elastic modulus values. The mean systolic arterial blood pressure in the patient group was determined to be lower than that of the control group. The mean diastolic wall stress values in the carotid and femoral arteries were determined to be lower than those of the control group. There was no relationship between antipsychotic dose, blood pressure and arterial stiffness parameters. Schizophrenia patients are more prone to develop arterial stiffness by atherosclerosis either with the effect of the nature of the disease itself or antipsychotic treatment. But evaluation with more parameters (carotid and femoral compliance, distensibility and elastic modulus) did not indicate any difference from the control group in respect of arterial stiffness. Antipsychotic treatment may play a protective role in terms of arterial stiffness by causing a decrease in systolic arterial pressure and carotid and femoral diastolic wall stress. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Vascular stiffness; Schizophrenia; Antipsychotic agents